Independence of basic arithmetic operations: Evidence from cognitive neuropsychology - Salguero-Alcañiz, María P.; Alameda-Bailén, José R. (Anales de Psicología / Annals of Psychology, 2013)
The cases described in literature evidence that arithmetical operations can function independently, which allows to infer that the cognitive processes involved in the different operations might be different. Objective of that work is to determine the different processes involved in the resolution of arithmetical operations: addition, subtraction and multiplication. Method. Instrument: Assesment of Numeric Processing and Calculation Battery (Salguero & Alameda, 2007, 2011). Subjects. Patients of acquired cerebral injury. Results and conclusions. The patient MNL preserves the addition and the multiplication but he presents altered the subtraction. On the contrary, the patient PP shows alterations in addition and multiplication but he conserves the skills for the subtraction. ISR presents a selective deficit for multiplication with intact addition and substraction. Finally, ACH preserves the addition but presents deficit for substraction and multiplication. This double dissociation confirms the postulates of the anatomical functional model of Dehaene and Cohen (1995, 1997) that consider a double route for the resolution of arithmetical simple operations: linguistic route, for numerical information learned automatically (of memory) and would be used for the operations of addition and multiplication, on the other hand the semantic elaboration would be for substraction.